Chronic Infection with Hidden Malignancy Mimicking the Clinical Presentation of an Autoimmune Disease - Ammar Bakhsh; Khalil Miyajan; Abdulghani Sadaqa; Amer Eisa; Ghali Faidah; Hani Almoallim (Case Reports in Rheumatology)
Infections of the paranasal sinuses are common and usually occur in patients who are immunocompromised. Many atypical clinical presentations have been reported but rarely in the elderly population. We report a 71-year-old female patient with a 20-year history of an autoimmune disease who had recently become resistant to treatment. Her autoimmune symptoms significantly improved following resection of deeply seated bacterial infection in her paranasal sinuses. She was also diagnosed with cervical cancer. Clinicians should look carefully for hidden infections and/or malignancies in patients lacking response while on immunosuppressive therapy for autoimmune disease.